Identification of co-expressed genes associated with MLL rearrangement in pediatric acute lymphoblastic leukemia. Issue 5 (7th May 2020) - Zhang, Hao; Liu, Bei; Cheng, Juan; Ma, Haizhen; Li, Zijian; Xi, Yaming
Abstract: Rearrangements involving the mixed lineage leukemia ( MLL ) gene are common adverse prognostic factors of pediatric acute lymphoblastic leukemia (ALL). Even allogeneic hematopoietic stem cell transplantation does not improve the outcome of ALL cases with some types of MLL rearrangements. The aim of the present study was to identify the co-expressed genes that related to MLL rearrangement ( MLL -r) and elucidate the potential mechanisms of how MLL -r and their partner genes lead to leukemogenesis. Gene co-expression networks were constructed using the gene expression data and sample traits of 204 pretreated pediatric ALL patients, and co-expression modules significantly related to the MLL -r were screened out. Gene ontology annotation and Kyoto Encyclopedia of Genes and Genomes pathway analysis of the module genes were performed. Hub genes were identified and their expression levels were analyzed in samples with or without MLL -r and the results were validated by an independent investigation. Furthermore, the relationships between the hub genes and sample traits were analyzed. In total, 21 co-expression modules were identified. The green module was positively correlated with MLL -r. PROM1, LGALS1, CD44, FUT4 and HOXA10 were identified as hub genes, which were involved in focal adhesion, calcium-dependent phospholipid binding, connective tissue development and transcriptional misregulation in cancer. The expression levels of the five hub genes were significantly increased in MLL -r samples, and the results were further validated. PROM1, LGALS1, CD44 and HOXA10 were positively related to the leukocyte count. These findings might provide novel insight regarding the mechanisms and potential therapeutic targets for pediatric ALL with MLL -r.